The Ideology of the British National Party - Jérôme Jamin (Revue LISA)
This article will explore the ideology of the British National Party (BNP). It will first examine the particular history of Extreme Right Parties (ERP) in England regarding other European countries and second, will look at the electoral evolution of the BNP. It will then take into account the current position of the BNP and assess whether the party still belongs to the ERP’s family. The concepts of “extreme right” and “populism” will be detailed and compared so as to argue that if the BNP is still part of the Extreme Right Parties’ family on some issues, it also belongs today to the populist family on other points, a family which is more “anti-elite”-oriented than purely racist, anti-Semitic or xenophobic. As a consequence, it will be shown that this current hybrid position might partially explain why BNP leaders can more easily participate in mainstream politics and public debates where they would have been previously banned.